QUANTIFYING THE COOLING EFFECT FOR URBAN PARK MICROCLIMATE: AN ANALYSIS OF PELTOPHORUM PTEROCARPUM SPECIES IN KLCC PARK, KUALA LUMPUR, MALAYSIA - Wan Ali @ Yaacob, Wan Noor Anira (PLANNING MALAYSIA, 2024)
Many cities worldwide are concerned with the urban heat island (UHI) effect. Rising temperatures negatively impact urban microclimates. However, vegetation can help to mitigate this effect. A particular tree species, Peltophorum pterocarpum (Yellow Flame) is the subject of this study's preliminary inquiry into its cooling effects. This study used a particular technique and statistical analysis to examine the unique cooling ability of Peltophorum pterocarpum in the urban park setting. This study will estimate the Peltophorum pterocarpum species' overall cooling effect by considering density and surface. It has led to a correlation coefficient of [0.75], signifying the magnitude and direction of the association between Peltophorum pterocarpum density and surface temperature. The species exhibits provided substantial shade coverage and resulting in a notable reduction in temperature. The outcomes of this research are expected to provide valuable insights for urban microclimate management, particularly in the context of parks and similar environments. By quantifying the cooling effect of Peltophorum pterocarpum, this study contributed evidence-based guidelines for urban planners and landscape designers, facilitating informed decision-making regarding vegetation selection and integration. Implementing these findings can effectively alleviate the urban heat island (UHI) effect, enhancing the liveability and sustainability of urban areas.